Uso de modelos numéricos no projeto do revestimento refratário de calcinadores para a produção de alumina - Pereira, Carolina Ierck (2024)
In the Bayer alumina production process, fluidized bed calciners use refractory linings to withstand erosive particles and temperatures above 900 °C. This work aims to enhance the geometric design of these linings by using Finite Element Method (FEM) to simulate their thermomechanical behavior, focusing on thermal analysis, layer interaction via friction coefficient, the impact of geometric parameters on thermal expansion and stresses, and expansion joint sizing. The results indicated that temperature-dependent properties and panel curvature altered the thermal gradient of the lining. However, variables such as the thickness of the working layer had a marginal impact on the temperature of the metal shell, suggesting low sensitivity of the external temperature to panel erosion. The friction coefficient between layers had minimal effect on thermal expansion, with a moderate increase in tensile stresses as the coefficient increased. Panel curvature had a significant impact, with curved panels expanding about 35 % more in the length direction compared to flat panels, affecting expansion joint design. Stresses concentrated at the edges of curved panels, while in flat panels, they were maximum at the center of the hot face. Empirical validation confirmed the effectiveness of the curved model and indicated the need to optimize anchor positioning to prevent crack propagation. Panel dimensions affected stresses, which increased with size and decreased with thickness, due to the balance between thermal gradient, moment of inertia, and bending moment. The ideal panel size was between 0.75 m and 1.0 m, balancing installation time and structural integrity. Proper material selection, such as reducing the thermal conductivity of the insulator, proved effective in reducing the likelihood of lining failure. Properly sizing expansion joints is essential to ensure both effective closure and structural stability.